Startups and Innovation Ecosystems in Emerging Markets A Brazilian Perspective - Oliveira, Jr., Moacir de Miranda; Cahen, Fernanda Ribeiro; Borini, Felipe Mendes (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XVI, 231 p. 21 illus., 8 illus. in color.